Wallace Stevens, Poetry, and France "Au pays de la métaphore" - Utard, Juliette; Eeckhout, Bart; Goldfarb, Lisa (Actes de la recherche à l'ENS, 2018)
Wallace Stevens, Poetry, and France offers the first book-length study of the various effects-poetic or prosaic, serious or comic, strange or familiar-produced by the deployment of French languages and cultures in Stevens' poetry. Prominent Stevens scholars reexamine here a number of key issues, from angles as diverse as translation studies, aesthetics, linguistics, comparative literature, French theory, and politics, raised by Stevens' special relation to France around the writing of poetry.